A Narrative of Resistance: A Brief History of the Dandara Community, Brazil - Beatriz Ribeiro; Fernando Oelze; Orlando Soares Lopes (Humanities, 2017)
This paper presents a brief report on the history of the Dandara Occupation, in the city of Belo Horizonte, Brazil. Through a general panorama of the strategies and resistance of the residents and movements involved; this paper shows the importance of the occupied territory in the struggle for the right to housing in the city. Through the narratives of the residents, references and photographic remnants of the initial years of the occupation, a temporal line is developed to the present day that reveals the challenges and opportunities for the people of Dandara in the making of their community.